Major clinical research advances in gynecologic cancer in 2022: highlight on late-line PARP inhibitor withdrawal in ovarian cancer, the impact of ARIEL-4, and SOLO-3 - Lee, Jung-Yun; Lee, Yoo-Young; Park, Jeong-Yeol; Shim, Seung-Hyuk; Kim, Se Ik; Kong, Tae-Wook; Lim, Chul Kwon; Cho, Hyun Woong; Suh, Dong Hoon (Journal of gynecologic oncology, 2023)
In the 2022 series, we summarized the major clinical research advances in gynecologic oncology based on communications at the conference of Asian Society of Gynecologic Oncology Review Course. The review consisted of 1) Ovarian cancer: long-term follow-up data, new poly (ADP-ribose) polymerase (PARP) inhibitors, overall survival (OS) issues with PARP inhibitor monotherapy, hyperthermic intraperitoneal chemotherapy, immunotherapy, and antibody-drug conjugate; 2) Cervical cancer: surgery in early stage disease, therapy for locally advanced stage and advanced, metastatic, or recurrent setting; and 3) Corpus cancer: follow-up regimen, immune checkpoint inhibitor, WEE1 inhibitor, selective inhibitor of nuclear export. A special note was made on the withdrawal of PARP inhibitor from the market for heavily pretreated ovarian cancer patients based on the final OS results of ARIEL-4 and SOLO-3 due to concerns of increased risk of death.